Ukrainian Fine Art in Canada (Second Half of the 20th Century) - Шалига, О. (Київський національний університет імені Тараса Шевченка, 2018)
The article highlights the process of incipience of Ukrainian fine art in Canada. During the second half of the 20th century the Ukrainian diaspora created its own art and multiplied traditional Ukrainian art. Unfortunately, the achievements of the Ukrainian diaspora as a rule aren't well-known to Ukrainian scientific community. The names of these people have filled up the treasury of spiritual values not only in Ukraine or Canada, but worldwide. Ukrainian artists from Canada have created artistic values reflecting the progress of the world's fine art and have retained the best traditions of native schools. The article contains information about such organizations as the Ukrainian Association of visual artists of Canada, the Ukrainian-Canadian Art Foundation, the Alberta Council for Ukrainian Art. The article also highlights life and artistic journey of V. Kurilyk, M. Dmitrenko, Leo Mol, G. Novakivska, O. Lesyuk, M. Antoniv.

Висвітлено процес становлення та розвитку образотворчого мистецтва українців на теренах Канади. Упродовж другої половини ХХ ст. українська діаспора створювала власне та примножувала традиційне українське мистецтво. Щоправда, досягнення української діаспори в Канаді є недостатньо відомими українській науковій громадськості. Імена цих людей поповнили скарбницю духовних цінностей не лише України чи Канади, але й усього світу. Українські митці Канади створили мистецькі цінності, що не лише відображали світовий образотворчий поступ, але й зберігали найкращі традиції вітчизняних шкіл. Розкрито діяльність таких організацій, як Українська спілка образотворчих митців, Канадсько-українська мистецька фундація, Альбертська рада українського мистецтва. Висвітлено також життєвий і творчий шлях визначних канадських митців українського походження В. Курилика, М. Дмитренко, Лео Мола, Г. Новаківської, О. Лесюка, М. Антонів.
Українське образотворче мистецтво в Канаді (друга половина ХХ ст.)
Keywords: fine art; Ukrainian diaspora; Canada; artist; образотворче мистецтво; українська діаспора; Канада; митець